Impact of social networks in promoting the right of citizenship and intellectual moderation from the perspective of Islam - LAYACHI, O. B (Utopía y Praxis Latinoamericana, 2019)
This study aims to identify the importance of using Social media networks in promoting citizenship and spreading the moderation culture basics to maintain the public security analytically, through reaching results that benefit in finding ways and means to achieve security and stability for the Muslims. By setting a historical approach and also to illustrate the noble Sunnah or the Islamic faith and trust principles, this study positions it as a moderator in order to help study the impact of social media networks in developing citizenship and civility as social platforms. RESUMEN Este estudio tiene como objetivo identificar la importancia del uso de las redes sociales en la promoción de la ciudadanía y la difusión de los principios básicos de la cultura de moderación para mantener la seguridad pública analíticamente, a través de alcanzar resultados que se beneficien al encontrar formas y medios para lograr la seguridad y la estabilidad de los musulmanes. Al establecer un enfoque histórico y también para ilustrar la noble Suena o los principios islámicos de fe y confianza, este estudio lo posiciona como moderador para ayudar a estudiar el impacto de las redes sociales en el desarrollo de la ciudadanía y la civilidad como plataformas sociales.